Safe and affordable pest management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Effective pest management and environmental safety are not easy to achieve where farm budgets are low. Participants at a Symposium in Kenya entitled 'Community-based and Environmentally Safe Pest Management' were warned that the high development and...